A study of significance of racial and athletic identification on educational perceptions among African American male college athletes. Issue 5 (3rd September 2017) - Fuller, Rhema D.; Harrison, C. Keith; Bukstein, Scott J.
Abstract: The purpose of this study was to analyze the racial and athletic identities of African American male college athletes to determine how the identities might impact the athletic and educational potential and performance of this specific group of college athletes. The study revealed that participants who responded negatively to a poor athletic performance were more likely to have lower levels of academic self-concept. In contrast, college athletes who highly identified with their racial group were more likely to have higher levels of academic self-concept. Overall, the findings reveal the intricacies and complexities of being an African American college student and athlete at predominantly white institutions (PWIs) in the US. As such, the article details the implications of the findings as they relate to African American culture, American sports culture, and higher education realities.